Preparation method, product and application of organic silicon elastomer material
By synthesizing anthracene derivatives and reacting them with polydimethylsiloxane and isophorone diisocyanate in one pot method, a silicone elastomer material with self-healing function was prepared, which solved the problem of low strength and fracture energy, and achieved excellent mechanical properties and self-healing properties.
Patent Information
- Application Number
- CN202510082701.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
During use, silicone elastomers have problems such as low strength, low breaking energy and prone to microcracks, which limits their application range.
By syntheses derivatives and reacting with aminopropyl-terminated polydimethylsiloxane and isophorone diisocyanate in one pot method, a silicone elastomer material with self-healing function was prepared. This material achieves self-healing through hydrogen bonding, and regulates mechanical properties and self-healing properties through the photoresponse of the anthracene structure.
It realizes excellent mechanical properties and good self-repair performance of silicone elastomer materials, and is suitable for the preparation of single-electrode friction nanogenerators and other applications that require self-repair function.
Smart Images

Figure CN119899123A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organosilicon elastomer preparation, and in particular to a preparation method, product and application of an organosilicon elastomer material. Background Art
[0002] As a device that detects and transmits information, it is crucial to develop applications that enhance or replace human intervention in equipment. Traditional sensors are mainly made of metals, semiconductors and other materials, with heavy weight, narrow measurement range and limited sensitivity. As a device that detects and transmits information, it is crucial to develop applications that enhance or replace human intervention in equipment. Traditional sensors are mainly made of metals, semiconductors and other materials, with heavy weight, narrow measurement range and limited sensitivity.
[0003] Flexible sensors have the characteristics of high sensitivity, fast response speed, wide measurement range, and non-destructiveness. They have broad application prospects in emerging fields such as wearable devices, human motion and health monitoring, electronic skin, and intelligent robots. Such sensors usually use flexible polymer materials as base materials, which makes them flexible, making them difficult to be destroyed by external forces and ensuring stable working signals.
[0004] Thanks to its special structure and unique physicochemical properties, silicone elastomers have good flexibility, hydrophobicity, biocompatibility, high chemical stability, non-toxicity and resistance to high and low temperatures. Based on these characteristics, silicone elastomers are widely used in many fields, and polydimethylsiloxane (PDMS) is one of the ideal matrix materials for flexible sensors. In recent years, researchers have prepared a variety of flexible sensors using PDMS as the matrix material, which has greatly promoted the development of this field. However, due to the low interchain interaction of silicon-oxygen bonds, the material has some significant disadvantages, such as low strength, low fracture energy, and easy microcracks under external stress. These shortcomings make the material susceptible to damage during its use, short service life and safety issues, which limits the application of silicone elastomers. Therefore, it is still a challenge to prepare polysiloxane elastomers with both good self-healing properties and excellent mechanical properties. Summary of the invention
[0005] Based on the above content, the present invention provides a silicone elastomer material with excellent mechanical properties and good self-healing properties.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is an anthracene derivative, the structural formula of which is as follows:
[0008]
[0009] The second technical solution of the present invention is a method for preparing the anthracene derivatives, which uses anthracenecarboxylic acid as a raw material and reacts it with 2-amino-2-methyl-1,3-propanediol to prepare the anthracene derivatives.
[0010] The third technical solution of the present invention is the use of the above-mentioned anthracene derivatives in the preparation of silicone elastomer materials.
[0011] A fourth technical solution of the present invention is a method for preparing an organosilicon elastomer material, comprising the following steps:
[0012] The aminopropyl-terminated polysiloxane and the organic solvent A are mixed to obtain a mixed solution 1;
[0013] Dissolving isophorone diisocyanate in organic solvent B to obtain a mixed solution 2;
[0014] Adding the mixed solution 2 to the mixed solution 1 and stirring under a nitrogen atmosphere to obtain a mixed solution 3;
[0015] The anthracene derivative is dissolved in organic solvent C and added to the mixed solution 3 to react under nitrogen atmosphere and catalyst conditions, and then methanol is added and allowed to stand to obtain a precipitate; the precipitate is dissolved in organic solvent D and allowed to stand to obtain the silicone elastomer material.
[0016] The fifth technical solution of the present invention is an organosilicon elastomer material prepared according to the above-mentioned preparation method of the organosilicon elastomer material. The hydrogen bonding effect in the structure of the organosilicon elastomer material gives it self-healing ability, and the anthracene structure gives the organosilicon elastomer material a photoresponsive effect, and the mechanical properties, self-healing properties and other properties are regulated by structural regulation to achieve the controllability of the performance.
[0017] The sixth technical solution of the present invention is a single-electrode friction nanogenerator, comprising a substrate material, a friction electric layer and an electrode layer; the friction electric layer comprises the above-mentioned silicone elastomer material. Due to the photoresponsiveness of anthracene, anthracene can be polymerized into dimers under corresponding ultraviolet light conditions; after dimerization, the conjugated system becomes larger, the electron donation ability becomes stronger, the electronegativity of the carbonyl group in the peptide bond becomes weaker, and the charge transfer is reduced after contact with the electrode layer, resulting in a decrease in the voltage of the friction nanogenerator. Subsequently, the anthracene dimer can be depolymerized under corresponding ultraviolet light conditions, thereby restoring the voltage. Based on this, it can be used as a self-powered sensor that can monitor the degree of polymerization of polymer dimerization.
[0018] The present invention discloses the following technical effects:
[0019] The present invention uses anthracenecarboxylic acid (ACA) as a raw material to synthesize an anthracene derivative (ACA-OH), and then uses aminopropyl-terminated polydimethylsiloxane (APT-PDMS), anthracene derivative (ACA-OH) and isophorone diisocyanate (IPDI) as raw materials to prepare a self-healing organosilicon elastomer material through a one-pot reaction. The organosilicon elastomer material has both good self-healing properties and excellent mechanical properties, and can be used to prepare a single-electrode friction nanogenerator. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 a) is the infrared spectrum (FTIR) of ACA-OH, b) is the nuclear magnetic resonance hydrogen spectrum analysis of ACA-OH ( 1 HNMR) results.
[0022] Figure 2 a) is the nuclear magnetic resonance hydrogen spectrum of the silicone elastomer material (IPA-2), and b) is the infrared spectrum of the silicone elastomer materials (IPA-1, IPA-2, IPA-3, IPA-4, IPA-5).
[0023] Figure 3 a) is the UV-visible absorption spectrum of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5, b) is the UV-visible absorption spectrum of IPA-2 under 365nm UV light conditions, and c) is the UV-visible absorption spectrum of IPA-2 after 365nm UV light irradiation and then 254nm UV light irradiation.
[0024] Figure 4 a) is the tensile stress-strain curve of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5; b) is the tensile stress-strain bar graph of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5.
[0025] Figure 5 Shown are the stress-strain curves of IPA-1a), IPA-2b), IPA-3c), IPA-4d), and IPA-5e) at different repair times.
[0026] Figure 6 Optical images of IPA-1 and IPA-2 before and after restoration.
[0027] Figure 7 The voltage change of IPA-3 under cyclic illumination at 365nm and 254nm. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] The "room temperature" described in the present invention, unless otherwise specified, refers to 20-30°C.
[0034] As a non-toxic and harmless polymer material, silicone is an important industrial commodity. Its Si-O bond structure gives it excellent performance, such as excellent physiological inertness, insulation, flexibility, hydrophobicity, low surface energy, high elasticity and low surface roughness. It has been widely used in electronics, flexible sensors, chemistry and medical equipment. However, polysiloxane elastomers will inevitably suffer from a series of problems such as wear, scratches and aging during use, which will affect their service life and safety. How to make silicone have both good mechanical properties and excellent self-healing properties is a problem that needs to be solved urgently.
[0035] The present invention combines the concept of self-repair with organosilicon to prepare materials with self-repair properties. Through the dissociation and reorganization of supramolecular action, the polymer can be dissolved and reshaped. This method can effectively reduce the cost of material use, the safety of the use process and other issues, and provides a more stable and economical solution in the practical application field. In addition, self-repairable materials with special functions also have potential applications in medical materials, soft robots and electronic skin.
[0036] The present invention uses anthracenecarboxylic acid (ACA) as a raw material to synthesize anthracene derivatives (ACA-OH), and then uses aminopropyl-terminated polydimethylsiloxane (APT-PDMS), anthracene derivatives (ACA-OH) and isophorone diisocyanate (IPDI) as raw materials to prepare a self-healing silicone through a one-pot reaction, and applies it to sensors for monitoring the degree of polymer dimerization. The mechanical properties, self-healing properties, thermal stability of the self-healing silicone elastomer material and the sensing performance of the silicone elastomer material as a UV strain sensor are systematically discussed. The research results are as follows:
[0037] (1) In this paper, anthracene derivatives (ACA-OH) were synthesized from anthracenecarboxylic acid (ACA);
[0038] (2) Using aminopropyl-terminated polydimethylsiloxane (APT-PDMS), anthracene derivative (ACA-OH) and isophorone diisocyanate (IPDI) as raw materials, a self-healing silicone elastomer material was prepared by a one-pot reaction;
[0039] (3) By synthesizing and designing a new type of silicone elastomer and adjusting the relative ratio of APT-PDMS, IPDI, and ACA-OH, a silicone elastomer material with excellent mechanical properties and self-healing effect is obtained;
[0040] (4) The purpose of introducing anthracene groups is to introduce a π-π stacked molecular structure into the elastomer network to further regulate the properties of the elastomer. The anthracene structure in the silicone elastomer matrix can be photosensitive. Therefore, the present invention designs an overall self-healing single-electrode TENG (IPA-TENG) based on APT-PDMS. According to the surface electrical properties, a self-powered sensor that can monitor the degree of polymerization of polymer dimerization is designed, and its performance and potential as a UV strain sensor are analyzed.
[0041] (5) Systematically test and analyze the mechanical properties, self-healing properties, etc. of the prepared silicone elastomer materials to provide theoretical support and experimental basis for subsequent formula design and material improvement.
[0042] The first aspect of the present invention provides an anthracene derivative, the structural formula of which is shown below:
[0043]
[0044] The second aspect of the present invention provides a method for preparing the anthracene derivatives, which uses anthracenecarboxylic acid as a raw material and reacts with 2-amino-2-methyl-1,3-propanediol to prepare the anthracene derivatives.
[0045] The third aspect of the present invention provides the use of the anthracene derivatives mentioned above in the preparation of silicone elastomer materials.
[0046] A fourth aspect of the present invention provides a method for preparing an organosilicon elastomer material, comprising the following steps:
[0047] The aminopropyl-terminated polysiloxane and the organic solvent A are mixed to obtain a mixed solution 1;
[0048] Dissolving isophorone diisocyanate in organic solvent B to obtain a mixed solution 2;
[0049] Adding the mixed solution 2 to the mixed solution 1 and stirring under a nitrogen atmosphere to obtain a mixed solution 3;
[0050] The anthracene derivative is dissolved in organic solvent C and added to the mixed solution 3 to react under nitrogen atmosphere and catalyst conditions, and then methanol is added and allowed to stand to obtain a precipitate; the precipitate is dissolved in organic solvent D and allowed to stand to obtain the silicone elastomer material.
[0051] In a preferred embodiment of the present invention, the molar ratio of the aminopropyl-terminated polysiloxane to the isophorone diisocyanate and the anthracene derivative is (7-11):12:(1-5).
[0052] In a preferred embodiment of the present invention, the reaction temperature is 60-65° C. and the reaction time is 12-16 hours.
[0053] In the present invention, if the reaction temperature is too low, the yield will be reduced; if the reaction temperature is too high, the boiling point of tetrahydrofuran will be reached, causing the reaction to explode; if the reaction time is too short, the reaction will be incomplete and the yield will be reduced; if the reaction time is too long, the yield will not be increased and the solvent will volatilize, affecting the performance of the system. Therefore, the present invention preferably limits the reaction temperature and time to the above parameter ranges.
[0054] In a preferred embodiment of the present invention, the organic solvent A, organic solvent B, organic solvent C and organic solvent D are all tetrahydrofuran.
[0055] A fifth aspect of the present invention provides an organosilicon elastomer material prepared according to the above-mentioned method for preparing an organosilicon elastomer material.
[0056] A sixth aspect of the present invention provides a single-electrode triboelectric nanogenerator (TENG), comprising a substrate material, a triboelectric layer and an electrode layer; the triboelectric layer comprises the above-mentioned silicone elastomer material.
[0057] In some embodiments of the present invention, the preparation of the single-electrode triboelectric nanogenerator (TENG) comprises the following steps:
[0058] Make sure the surface of the polymethyl methacrylate (PMMA) board is clean and flat so that the copper foil can adhere tightly to it; when pasting the copper foil, make sure that the copper foil is flat, bubble-free, and fits tightly to the PMMA board. Cut the above silicone elastomer material to a size of 2cm×2cm, and bond it to a glass slide and integrate it onto the PMMA board as the triboelectric layer of the TENG, with the copper foil as the electrode. Finally, connect the copper foil to the probe of the programmable electrometer through a wire.
[0059] As a high-quality packaging material, polymethyl methacrylate (PMMA) has excellent insulation properties, mechanical strength and chemical stability, making it an ideal substrate material for TENG. It plays a key role in connecting the positive and negative electrodes of TENG with the linear motor.
[0060] The test method involved in the present invention is as follows:
[0061] 1. Infrared spectroscopy (FT-IR)
[0062] Infrared spectroscopy was performed on a Nicolet 6700 spectrometer with a scan range of 4000–500 cm -1 , the scanning times are 4 times, and the resolution is 4cm -1 For powder samples, potassium bromide tableting was used for testing. A small amount of sample was mixed evenly with a certain amount of potassium bromide, and then pressed into tablets after grinding. For solid film samples, total reflection (ATR-FTIR) mode was used for testing.
[0063] 2. Nuclear magnetic resonance spectroscopy ( 1 H-NMR)
[0064] The structures of ACA-OH and IPA were verified using a BrukerAvance 400 NMR spectrometer from Bruker, Switzerland. They were dissolved in deuterated CDCl3 and tested using liquid NMR.
[0065] 3. Solid UV (UV-Vis)
[0066] The UV-visible absorption spectrum of the thin film sample was measured by a Hitachi U-3900 spectrometer at 298 K in the absorption mode. The absorption spectrum of the sample in the wavelength range of 320-420 nm was detected once every certain period of irradiation with 365 nm UV light.
[0067] 4. Tensile performance test
[0068] The tensile strength and elongation at break of the system were tested using a C41.104 microcomputer-controlled electronic universal testing machine produced by Xinsansi (Shanghai) Enterprise Development Co., Ltd. The upper limit of the sensor was 100 N. The test speed was 50 mm / min and the test temperature was 25°C.
[0069] The tensile strength is calculated as follows:
[0070]
[0071] Where: S —Tensile strength of silicone elastomer material, MPa;
[0072] F—The maximum load corresponding to the fracture of the silicone elastomer material, N;
[0073] b—width of silicone elastomer material, mm;
[0074] h—length of silicone elastomer material, mm.
[0075] The elongation at break of the sample is calculated as follows:
[0076]
[0077] Where: E—elongation at break of silicone elastomer material, %;
[0078] l—Clamp distance when the silicone elastomer material breaks, mm;
[0079] l0—Original standard fixture distance, mm.
[0080] 5. Self-healing performance test
[0081] First, the long strip sample was cut into two halves with a blade to allow the fracture surfaces to fully contact each other. Then, different samples were placed at room temperature for different periods of time for repair, and the self-healing process was observed using an optical microscope.
[0082] An MP41 polarizing microscope produced by Guangzhou Huayu Instrument Technology Co., Ltd. was used to observe the changes in the surface morphology of the system before and after self-repair, and images of the system before, after and after scratching were obtained.
[0083] Different samples were placed at room temperature for different time periods for repair. In order to test the stress-strain curve of the repaired samples, the samples were broken again with a tensile machine after healing for 12 hours, 24 hours, and 48 hours, and the repair efficiency of the samples was calculated through the stress-strain curve.
[0084] The self-repair efficiency is calculated as follows:
[0085]
[0086] Where: η—self-repair efficiency, %;
[0087] S healed —Maximum tensile strength of the repaired specimen, MPa;
[0088] S original —Maximum tensile strength of original specimen, MPa.
[0089] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0090] The meanings of the English abbreviations in the present invention are as follows:
[0091] HOBt: 1-Hydroxybenzotriazole
[0092] EDCI: 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride
[0093] APT-PDMS: aminopropyl terminated polysiloxane
[0094] THF: Tetrahydrofuran
[0095] IPDI: Isophorone diisocyanate
[0096] DBTDL: Dibutyltin dilaurate
[0097] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0098] Example 1
[0099] (1) Preparation and structural characterization of anthracene derivatives (ACA-OH)
[0100] Anthracene derivatives (ACA-OH) were prepared using anthracenecarboxylic acid as a raw material. The steps are as follows:
[0101] Anthracenecarboxylic acid (0.733 g, 3.3 mmol) and 1-hydroxybenzotriazole (0.536 g, 3.9 mmol) were added to a three-necked round-bottom flask equipped with a magnetic stirrer. Then, under a nitrogen atmosphere, 15 mL of N,N-dimethylformamide (15-20 mL) was injected into the flask with a syringe. The mixture was stirred in an ice bath for 0.5 h to activate the carboxyl group. Stirring was stopped, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added to the flask, and stirring was continued for 0.5 h. After removing the ice bath, (0.521 g, 4.9 mmol) of 2-amino-2-methyl-1,3-propanediol and (0.685 g, 4.9 mmol) of potassium carbonate solid were added in sequence, and stirred at room temperature for 24 h to obtain a yellow-brown solution and a small amount of white precipitate. The yellow-brown solution was extracted with ethyl acetate to obtain a light yellow solution, which was separated and purified by dry column chromatography, with a solution of methanol and dichloromethane in a volume ratio of 1:20 as the developing solvent, to obtain a light yellow solution, which was spin-dried and dried at 60°C for 1h to obtain a light yellow solid (ACA-OH). The reaction process is as follows:
[0102]
[0103] The structure of ACA-OH was characterized by infrared spectrum (FTIR). Figure 1 As shown in a), its nuclear magnetic resonance hydrogen spectrum analysis ( 1 H NMR) Figure 1 As shown in b), Figure 1 ACA in the figure indicates anthracenecarboxylic acid. The infrared spectrum shows that 3345 cm -1 and 1533cm -1 The characteristic peaks at 2925cm are the stretching vibration and bending vibration of NH. -1 It is the stretching vibration peak of methylene, 1734cm -1 is the stretching vibration peak of methyl group, and 1045cm -1 The peak at 1625cm is the characteristic peak of CC single bond stretching vibration. -1 The stretching vibrations corresponding to the carbonyl group were found at 1645 cm-1, and the amide I band (-CO-) and amide II band (-NH-stretching vibration) were assigned to -1 and 1533cm -1 The peaks indicate the successful synthesis of anthracene derivatives. Figure 1 b) shows the polymer1 HNMR, which also proved the successful synthesis of ACA-OH.
[0104] (2) Preparation and structural characterization of silicone elastomer materials
[0105] To screen out the best ratio of silicone elastomer materials, the steps are as follows:
[0106] a. Add aminopropyl-terminated polysiloxane (Mn=3000) (3.0 g, 1.0 mmol) into a three-necked round-bottom flask equipped with a magnetic stirrer, evacuate the mixture in an oil bath at 100°C for 30 min, cool to room temperature, add 10 mL of anhydrous tetrahydrofuran to the flask, and mix well.
[0107] b. Add isophorone diisocyanate (0.267 g, 1.2 mmol) to a beaker and add 5 mL of anhydrous tetrahydrofuran to dissolve. After complete dissolution, pour the solution in the beaker into a constant pressure funnel and add the mixed solution to the above APT-PDMS THF solution. The reaction was carried out under nitrogen atmosphere protection. After stirring at room temperature for 24 hours, a THF solution of APT-PDMS-NCO was obtained. The next step of the reaction can be carried out without further treatment.
[0108] c. Add ACA-OH (0.0615g, 0.2mmol) to a beaker, and add 3mL of anhydrous tetrahydrofuran to dissolve it. After it is completely dissolved, add the solution in the beaker to the above three-necked flask and add 3μl of dibutyltin diacid catalyst. The reaction is carried out under a nitrogen atmosphere at 60℃. After stirring for 12h, pour the reaction solution into a beaker, add 5 times the volume of methanol of the reaction solution to the beaker, precipitate a white viscous substance, let it stand for 12h, pour off the supernatant, add 2mL of tetrahydrofuran to dissolve the white viscous substance, pour it into a custom polytetrafluoroethylene mold (length 11cm, width 9cm) and leave it at room temperature for 24h to obtain a colorless and transparent silicone elastomer material with a length of 30mm and a width of 10mm. The reaction process is as follows:
[0109]
[0110] Based on step (2), the amounts of APT-PDMS, IPDI and ACA-OH were adjusted as shown in Table 1, and the corresponding silicone elastomer materials were marked as IPA-1, IPA-2, IPA-3, IPA-4 and IPA-5, respectively.
[0111] Table 1
[0112]
[0113] The structure of the prepared silicone elastomer material was characterized by ultraviolet-visible absorption spectroscopy (UV-Vis), infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy ( 1 1H NMR).
[0114] Figure 2 a) is the H NMR spectrum of IPA-2, and b) is the infrared spectrum results of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5. The infrared spectrum results show that 3345 cm -1 and 1570cm -1 The characteristic peaks at 2960cm are the stretching vibration and bending vibration of NH. -1 is the stretching vibration peak of methylene, and 1260cm -1 The peak at 1625cm is the characteristic peak of CC single bond stretching vibration. -1 The stretching vibration corresponding to the carbonyl group was found at 1005 cm -1 The peak at 785 cm is related to the asymmetric stretching vibration of the Si-O-Si main chain of IPA. -1 The stretching vibration of CH on the anthracene ring proves the successful preparation of the silicone elastomer system. In addition, all silicone elastomers in all formulations have the same infrared peak performance, proving that silicone elastomers in different formulations have similar molecular chain structures.
[0115] Figure 3 Figure a) is the UV-visible absorption spectra of IPA-1, IPA-2, IPA-3, IPA-4 and IPA-5. The characteristic absorption peaks at 329, 347, 363 and 384 nm are attributed to the anthracene group, indicating that anthracene is successfully introduced into the IPA-X (X=1, 2, 3, 4, 5) elastomer. Figure 3 b) is the UV-visible absorption spectrum of IPA-2 at different irradiation times at 365 nm. As the irradiation time increases, the intensity of the four peaks gradually decreases, which is due to the dimerization of anthracene on the polymer chain. This phenomenon indicates that the photocrosslinking reaction is efficient. Subsequently, the sample was exposed to 254 nm UV light to dissociate the anthracene dimer into monomers, such as Figure 3 As shown in Figure c), as the 254nm irradiation time increases, the peak intensity of the characteristic absorption peak of anthracene gradually increases. This phenomenon can be attributed to the dissociation of anthracene dimers and the regeneration of consumed anthracene groups. The result ensures the occurrence of anthracene cross-linking and de-cross-linking of anthracene dimers, which is achieved by alternating ultraviolet irradiation of different wavelengths.
[0116] The prepared silicone elastomer material was characterized in terms of its mechanical properties and self-healing properties.
[0117] The tensile properties of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5 were characterized by a stretching machine. Figure 4 a) is the stress-strain curve of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5, and b) is the stress-strain bar graph of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5.
[0118] Depend on Figure 4 It can be seen that the tensile strength and elongation at break of IPA-5 elastomer are the lowest, which are 1.31±0.23MPa and 409±35% respectively. The elongation at break of IPA-1 is the highest, which is about 1886%, while the tensile strength is about 1.90MPa. The results show that with the decrease of the content of aminopropyl-terminated polysiloxane and the increase of ACA-OH content, the strength of the elastomer first increases and then decreases. On the one hand, the introduction of ACA-OH significantly improves the mechanical properties of the material due to the increase of the rigid benzene ring structure. On the other hand, further increasing the amount of ACA-OH will reduce the strength and self-healing ability of the elastomer. The reason may be that the excessive Π-Π stacking of anthracene structure destroys the microstructure of the elastomer, thereby affecting the mechanical properties, and the steric effect prevents the migration of the chain, thereby reducing the self-healing efficiency. By adjusting the ratio of polysiloxane and anthracene derivatives, the stress strain of the elastomer can be effectively controlled. Explore the best mechanical properties of the elastomer and find a suitable ratio to adapt to different work contents. IPA-X has the best comprehensive performance of IPA-2 elastomer, whose tensile stress reaches about 2.15±0.25MPa and elongation at break reaches 1614±29%.
[0119] Figure 5 The stress-strain curves of IPA-1, IPA-2, IPA-3, IPA-4 and IPA-5 at different repair times (in the figure, Original represents the tensile strength of the original silicone elastomer materials IPA-1 and IPA-2 before repair; 12h, 24h and 48h represent the tensile strength measured 12h, 24h and 48h after the fracture). Figure 5 It can be seen in a) that after 12 hours of healing, the self-healing efficiency of IPA-1 recovered to 59.7%. When the healing time was further extended to 48 hours, the self-healing efficiency was as high as 87.4%. Figure 5 As can be seen in b), after 12 hours of healing, the self-healing efficiency of IPA-2 recovered to 66.0%. When the healing time was further extended to 48 hours, the self-healing efficiency was as high as 90.7%. Figure 6 Optical microscope photos of IPA-1 and IPA-2 before and after restoration; Figure 6As shown, the scratches on the IPA film almost completely disappeared after 24 h of repair, further demonstrating the self-healing ability of IPA at room temperature.
[0120] The mechanical properties and repair performance data of IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5 are shown in Table 2.
[0121] Table 2
[0122]
[0123] IPA-1, IPA-2, IPA-3, IPA-4 and IPA-5 prepared in the examples of the present invention were applied to the preparation of a single-electrode triboelectric nanogenerator (TENG):
[0124] The preparation of a single-electrode triboelectric nanogenerator (TENG) includes the following steps:
[0125] Make sure the surface of the polymethyl methacrylate (PMMA) board is clean and flat so that the copper foil can adhere tightly to it; when pasting the copper foil, make sure that the copper foil is flat, bubble-free, and fits tightly to the PMMA board. Cut the above silicone elastomer material to a size of 2cm×2cm, and bond it to a glass slide and integrate it onto the PMMA board as the triboelectric layer of the TENG, with the copper foil as the electrode. Finally, connect the copper foil to the probe of the programmable electrometer through a wire.
[0126] The voltage changes of IPA-1, IPA-2, IPA-3, IPA-4 and IPA-5 prepared in the embodiment of the present invention before and after irradiation (365nm) are shown in Table 3.
[0127] Table 3
[0128]
[0129]
[0130] Table 3 shows the voltage changes of silicone elastomer materials IPA-1, IPA-2, IPA-3, IPA-4, and IPA-5 before and after light irradiation (365nm). After comparison, it is found that under the same irradiation time, the voltage change amplitude of IPA-3 is the most obvious. Subsequent device applications will be based on IPA-3 as the research object.
[0131] Figure 7The voltage changes of IPA-3 under 365nm and 254nm illumination. After 365nm illumination, the voltage drops after the anthracene groups are cross-linked. Subsequently, the sample is exposed to 254nm ultraviolet light, causing the anthracene dimer to dissociate into monomers, resulting in an increase in the number of peaks and a voltage rebound. This further proves the reversibility of the structure of anthracene and anthracene dimer under corresponding external conditions. In order to prove the reversibility of the designed network, we repeated the above operation, and the results are shown in Figure 7 shown.
[0132] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An anthracene derivative, characterized in that: The structural formula is as follows:
2. The method for preparing anthracene derivatives according to claim 1, characterized in that: Anthracenecarboxylic acid is used as a raw material and reacted with 2-amino-2-methyl-1,3-propanediol to prepare the anthracene derivative.
3. Use of the anthracene derivative according to claim 1 in the preparation of organic silicon elastomer materials.
4. A method for preparing an organosilicon elastomer material, characterized in that: The following steps are involved: The aminopropyl-terminated polysiloxane is mixed with the organic solvent A to obtain a mixed solution 1; Dissolving isophorone diisocyanate in organic solvent B to obtain a mixed solution 2; Adding the mixed solution 2 to the mixed solution 1 and stirring under a nitrogen atmosphere to obtain a mixed solution 3; The anthracene derivative described in claim 1 is dissolved in organic solvent C and added to the mixed solution 3, reacted under nitrogen atmosphere and catalyst conditions, and then methanol is added and allowed to stand to obtain a precipitate; the precipitate is dissolved in organic solvent D and allowed to stand to obtain the silicone elastomer material.
5. The method for preparing an organosilicon elastomer material according to claim 4, characterized in that: The molar ratio of the aminopropyl-terminated polysiloxane to the isophorone diisocyanate and anthracene derivative is (7-11):12:(1-5).
6. The method for preparing an organosilicon elastomer material according to claim 4, characterized in that: The reaction temperature is 60-65°C and the reaction time is 12-16 hours.
7. The method for preparing an organosilicon elastomer material according to claim 4, characterized in that: The organic solvent A, organic solvent B, organic solvent C and organic solvent D are all tetrahydrofuran.
8. The organosilicon elastomer material prepared according to the method for preparing an organosilicon elastomer material according to any one of claims 4 to 7.
9. A single-electrode friction nanogenerator, characterized in that: It comprises a base material, a triboelectric layer and an electrode layer; the triboelectric layer comprises the organic silicon elastomer material according to claim 8.